Auch zu Weihnachten keine Geschenke! - Lieb, Klaus; Koch, Cora (DMW - Deutsche Medizinische Wochenschrift, 2017)
Gifts and payments from pharmaceutical manufacturers to medical doctors constitute a conflict of interest, which may lead to an undue influence on prescribing behavior. In Germany, 35 research-based pharmaceutical companies, organized in the “Verband der forschenden Arzneimittelhersteller (VfA)” paid € 562 million to medical doctors and hospitals in 2016. Of these, € 356 million were paid for clinical trials and non-interventional studies, € 105 million for sponsored presentations and CME and € 101 million went to hospitals and other organizations for sponsoring, consulting and events. This article gives a short review on the different kinds of interactions, discusses psychological mechanisms and legal aspects of accepting gifts and recommends not to accept any gifts and donations from pharmaceutical companies to avoid undue influences on prescribing behavior. There are many ways to keep up to date using independent sources of information, and independent CME-events are growing in number – examples are given.
Keywords: Interessenkonflikte; Pharmazeutische Industrie; Unabhängigkeit; Korruption; ärztliche Fortbildung